A Contextual Scientometric Analysis of Indonesian Biomedicine : Mapping The Potential of Basic Research Downstreaming - Ria Hardiyati; Irene Muflikh Nadhiroh; Tri Handayani; V.M. Mesnan Silalahi; Rizka Rahmaida; Mia Amelia (Center for Science and Technology Development Studies, Indonesian Institute of Sciences, 2018)
A content analysis on Indonesian biomedical research publication is conducted based on text mining. The research is necessary to obtain a rich contextual overview of the development of biomedicine research in Indonesia for example in the context of the downstreaming potential of research publications. The results of text data processing using a computational model and bibliometric analysis will provide a richer contextual picture as a proxy to reveal the potential for downstreaming of basic research. Quantitative research is conducted using data sources from Scopus, Google Scholar and universities’s and scientific journal’s repository to analyse the performance at the meso and macro level. Interpretation of the results is qualitatively carried out within a FGD session with domain experts. An attempt is carried out to see the trajectory of series of research publications from basic research stage down to clinical trials. This effort results in an ability to show the research trajectory in anti-malaria drug development from the basic research which evolves to the clinical trial. This study reveals many discontinuities in the trajectory a research topic from basic research to downstreaming in drugs development in Indonesia.